1983
DOI: 10.1007/bf00279400
|View full text |Cite
|
Sign up to set email alerts
|

In vitro expression of α-l-fucosidase activity polymorphism observed in plasma

Abstract: Several quantitative and qualitative characteristics of alpha-L-fucosidase were studied in cultured skin fibroblasts derived from variant and non-variant individuals. In comparison with non-variant cultures with similar growth characteristics, the intracellular level of alpha-L-fucosidase was specifically reduced by at least 50% at all stages of the culture cycle. The amount of enzyme released into the growth medium was also decreased, but the ratio of the extracellular enzyme to the total enzyme activity prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…23,24,26 Variants have also a lower fucosidase activity in cultured fibroblasts. 27 In leucocytes and lymphoblastoid cell lines, however, the fucosidase activity of variants and normals is not significantly different. 23,24 All eight FUCA1 exons and exon-intron boundaries from individuals who were homozygous for the low activity trait, were sequenced but no mutation was found (Seo and O'Brien, unpublished results).…”
Section: Low Plasma Activity Polymorphism In Fuca2mentioning
confidence: 95%
“…23,24,26 Variants have also a lower fucosidase activity in cultured fibroblasts. 27 In leucocytes and lymphoblastoid cell lines, however, the fucosidase activity of variants and normals is not significantly different. 23,24 All eight FUCA1 exons and exon-intron boundaries from individuals who were homozygous for the low activity trait, were sequenced but no mutation was found (Seo and O'Brien, unpublished results).…”
Section: Low Plasma Activity Polymorphism In Fuca2mentioning
confidence: 95%
“…In human, there are two isoforms of AFUs, namely FUCA1 and FUCA2 that are predominantly localized in the tissues such as liver 11 , as well as plasma and fibroblasts 12 , respectively. FUCA1 is encoded by a gene on chromosome 1p (1p34) 13 and FUCA2 is encoded by a gene linked to plasminogen on chromosome 6 (6q24) 14 .…”
Section: The Structural Characteristics and Function Of Afusmentioning
confidence: 99%
“…The uptake of radiolabelled fucose into skin fibroblasts was normal.Studies of serum and teukocytes from clinically normal individuals have revealed an enzyme variant exhibiting low activity and increased lability (Ramage and Cunningham, 1975). A recent report (Van Elsen et al, 1983) has demonstrated that the specific features of the variant enzyme are expressed in variant fibroblasts. The reaction kinetics, pH optima and Km values are similar for variant and nonvariant fucosidases.…”
mentioning
confidence: 99%